Some factors affecting milk yield of Holstein-Friesian dairy cows imported to Ghot-Al Sultan Project (Libya) - Amaizik, Amaizik, S. A; Amir, M. A. (Al-Mukhtar Journal of Sciences, 2015)
This study was carried out to determine the effects of calf sex, insemination system (artificial or natural service) and number of services per conception on milk yield of dairy cows. 160 production records of Holstein-Friesian dairy cows (age 3-5 years) imported to Ghot-Al Sultan Project (Libya) were studied. The milk yield of the first five months of lactation season (during year, 2004) was used. Average monthly milk yield was also included in the study. The results of study showed that, daily milk yield of cows which calved males was significantly (P